Model and Reduction of Inactive Times in a Maintenance Workshop Following a Diagnostic Error - Meva'a, L.; Danwe, R.; Beda, T. (Engineering, Technology & Applied Science Research, 2011)
The majority of maintenance workshops in manufacturing factories are hierarchical. This arrangement permits quick response in advent of a breakdown. Reaction of the maintenance workshop is done by evaluating the characteristics of the breakdown. In effect, a diagnostic error at a given level of the process of decision making delays the restoration of normal operating state. The consequences are not just financial loses, but loss in customers’ satisfaction as well. The goal of this paper is to model the inactive time of a maintenance workshop in case that an unpredicted catalectic breakdown has occurred and a diagnostic error has also occurred at a certain level of decision-making, during the treatment process of the breakdown. We show that the expression for the inactive times obtained, is depended only on the characteristics of the workshop. Next, we propose a method to reduce the inactive times.